Sistem Keputusan dengan Metode Multi Attribute Utility Theory dalam Penilaian Kinerja Pegawai - Fuad El Khair; Sarjon Defit; Y Yuhandri (SEULANGA SYSTEM PUBLISHER, 2021)
In an agency, it takes an employee who is able to carry out the work in accordance with the objectives in achieving a target becomes an assessment by the leaders. Not only attendance, but also leadership, commitment, cooperation, discipline, service orientation, integrity and ability to perform the task given also need to be used as an indicators . The purposes aim to motivate employees to be passionate in doing every activity and to have a positive influence on their work in facing challenges of globalization. Decision Support System is a need. It is called a Multi Attribute Utility Theory method is a quantitative comparison method that usually combines measurements of different risk costs and benefits. The data processed for employee performance assessment in this study as many as 20 samples sourced from the Population and Civil Registration Office of Pesisir Selatan Regency. This based on several specified criteria and weights. There are 6 data that are used in it. Such as service orientation, integrity, commitment, discipline, cooperation and employee performance goals. The result is able to support employee decisions using predetermined criteria. So that highest value is in the 6th alternative with a value of 1.8 and the lowest value on the 16th alternative with a value of 0. Later it will be a consideration for Population and Civil Registry Office of South Coast Regency to assess its employees in certain period. Employee performance assessment is proven to be able to help the South Coast Population and Civil Registration Office.